Evaluation of wheat chromosome translocation lines for high temperature stress tolerance at grain filling stage - Pradhan, Gautam Prasad; Prasad, P. V. Vara (My University, 2015)
High temperature (HT, heat) stress is detrimental to wheat (Triticum aestivum L.) production. Wild relatives of bread wheat may offer sources of HT stress tolerance genes because they grow in stressed habitats. Wheat chromosome translocation lines, produced by introgressing small segments of chromosome from wild relatives to bread wheat, were evaluated for tolerance to HT stress during the grain filling stage. Sixteen translocation lines and four wheat cultivars were grown at optimum temperature (OT) of 22/14°C (day/night). Ten days after anthesis, half of the plants were exposed to HT stress of 34/26°C for 16 d, and other half remained at OT. Results showed that HT stress decreased grain yield by 43% compared with OT. Decrease in individual grain weight (by 44%) was the main reason for yield decline at HT. High temperature stress had adverse effects on leaf chlorophyll content and Fv/Fm; and a significant decrease in Fv/Fm was associated with a decline in individual grain weight. Based on the heat response (heat susceptibility indices, HSIs) of physiological and yield traits to each other and to yield HSI, TA5594, TA5617, and TA5088 were highly tolerant and TA5637 and TA5640 were highly susceptible to HT stress. Our results suggest that change in Fv/Fm is a highly useful trait in screening genotypes for HT stress tolerance. This study showed that there is genetic variability among wheat chromosome translocation lines for HT stress tolerance at the grain filling stage and we suggest further screening of a larger set of translocation lines.
Citation: Pradhan GP, Prasad PVV (2015) Evaluation of Wheat Chromosome Translocation Lines for High Temperature Stress Tolerance at Grain Filling Stage. PLoS ONE 10(2): e0116620. doi:10.1371/journal.pone.0116620
Keywords: Wheat; High temperature stress tolerance; Wheat chromosome translocation lines